Bone Cement Implantation Syndrome in the Perioperative Period of Large Joint Endoprosthesis - I. A. Tomashevsky; Ye. V. Grigoryev; A. S. Razumov; G. A. Li; G. V. Vavin (Общая реаниматология)
Objective: to enhance the efficiency of diagnosis of and intensive therapy for bone cement implantation syndrome in the perioperative period of endoprosthesis of large joints of the lower extremity.Subjects and methods: A study group comprised 18 patients who received standard perioperative intensive therapy for the bone cement implantation syndrome. A control group included 22 patients in whom perioperative correction of hemostatic disorders was made, by including 6% solution into the infusion program of second-generation hydroxyethyl starches (200/0.5) and by postoperatively administering low molecular-weight heparins. To evaluate the state of the basic hemostatic links, the classical laboratory parameters were determined, as described by Z. S. Barkagan, et al. Concurrent with the determination of the classical parameters, an integral estimate was made by rapid blood viscosimetry.Results. Impairments of basic hemostatic links in the bone cement implantation syndrome are characterized by the development of prethrombosis. Rapid blood viscometric parameters, such as the rate of spontaneous platelet aggregation, the onset of clotting, the constants of thrombin, blood clotting, total blood clotting, a fibrin-platelet constant, and the cumulative rate of clot retraction and lysis, correlate with classical biochemical parameters.Conclusion. The pathogenetically warranted use of a combination of low molecular-weight heparin and second-generation hydrox-yethyl starch enhances the efficiency of correction of perioperative impairments of the basic hemostatic links in the cement endoprosthetic replacement of large joints of the lower extremity.